1999
DOI: 10.1366/0003702991946749
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Effect Studies in the Inductively Coupled Plasma with Monodisperse Droplets. Part I: The Influence of Matrix on the Vertical Analyte Emission Profile

Abstract: The effects of different matrices on the analyte vertical emission profile in the inductively coupled plasma were evaluated with use of a monodisperse droplet sample introduction system in combination with a pneumatic nebulizer. The influence of matrix in the gas phase was separated from influences in the desolvation and volatilization steps. The results suggest that vertical shifts in the analyte emission profiles occur primarily during droplet desolvation and vaporization. The vertical shifts can be correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 25 publications
1
28
0
Order By: Relevance
“…It has been suggested that this earlier volatilization might be the consequence simply of the higher sample concentration displacing some of the solvent in each droplet of a given size. 39 Availability of images for the various plasma features also enables likely mechanisms of atomic or ionic excitation to be identified. Each such mechanism is assumed to be kinetically controlled but to be in steady state at any given location in the plasma.…”
Section: Analytical Sciences November 2002 Vol 18mentioning
confidence: 99%
“…It has been suggested that this earlier volatilization might be the consequence simply of the higher sample concentration displacing some of the solvent in each droplet of a given size. 39 Availability of images for the various plasma features also enables likely mechanisms of atomic or ionic excitation to be identified. Each such mechanism is assumed to be kinetically controlled but to be in steady state at any given location in the plasma.…”
Section: Analytical Sciences November 2002 Vol 18mentioning
confidence: 99%
“…Plasma-related non-spectroscopic matrix effects from easily ionizable elements (such as K, Na) and other matrices (such as HNO 3 , H 2 SO 4 ) cause analyte signal suppression or enhancement in inductively coupled plasma-atomic emission spectrometry (ICP-AES) [1][2][3][4][5][6][7][8][9][10][11][12]. Matrix effects remain an important yet not fully understood phenomenon in plasma emission spectrometry [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix effects remain an important yet not fully understood phenomenon in plasma emission spectrometry [12][13][14][15]. Different mechanisms have been proposed for the plasma-related non-spectroscopic matrix interferences in ICP-AES including increased collisional excitation [1][2][3][4][5], ambipolar diffusion [1], shift in analyte-ionization equilibrium [1][2][3], ion-electron recombination [5][6][7], lateral diffusion [2][3][8][9], change in energy distribution of species that collide with and excite the analyte [10] and change in excitation conditions of the plasma [11]. So far there is no agreement on the dominant mechanism [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations